Hepcidin and erythroferrone response to 3 weeks of exposure to normobaric hypoxia at rest in trained cyclists - Płoszczyca, Kamila; Czuba, Miłosz; Chalimoniuk, Małgorzata; Witek, Konrad; Baranowski, Marcin (Frontiers in Physiology, 2023)
The effectiveness of altitude training on haematological adaptations is largely dependent on iron metabolism. Hepcidin and erythroferrone (ERFE) are key iron-regulating hormones, yet their response to altitude training is poorly understood. The aim of this study was to analyze changes in hepcidin and ERFE under the influence of 3 weeks of the Live High-Train Low (LH-TL) method. Methods: Twenty male trained cyclists completed a 3-wk training program under normoxic conditions (NORM) or with passive exposure to normobaric hypoxia (LH-TL; FiO 2 =16.5%, ~2000 m; 11-12h/day). Hepcidin, ERFE, hypoxia inducible factor-2 (HIF-2), ferroportin (Fpn), erythropoietin (EPO), serum iron (Fe) and hematological variables were assessed at baseline (S1), then immediately after (S2) and 3 days after (S3) intervention. Results: In the LH-TL group, hepcidin decreased by 13.0% (p<0.001) in S2 and remained at a reduced level in S3. ERFE decreased by 28.7% (p<0.05) in S2 and returned to baseline in S3. HIF-2α decreased gradually, being lower by 25.3% (p<0.05) in S3. Fpn decreased between S1 and S2 by 18.9% (p<0.01) and remained lower during S3 (p<0.01). In the NORM group, in turn, hepcidin levels increased gradually, being higher by 73.9% (p<0.05) in S3 compared to S1. No statistically significant differences in EPO were observed in both groups. Conclusions: Three weeks of LH-TL suppresses resting hepcidin and ERFE levels in endurance athletes. We found no association between hepcidin and ERFE after LH-TL. Probably, ERFE is not the only factor that suppresses hepcidin expression in response to moderate hypoxia, especially in later stages of hepcidin down-regulation. With the cessation of hypoxia, favorable conditions for increasing the availability of iron cease.